Pengaruh Ruang Publik Terhadap Kualitas Visual Jalan Kali Besar Jakarta - Dedi Hantono (Universitas Sebelas Maret Surakarta, 2017)
Kali Besar is a river that stretches from South to North and there are two roads on both sides, namely: Jalan Kali Besar Barat and Jalan Kali Besar Timur. On the government's awareness of the importance of preservation of buildings and historic areas, since 2008 the City of Jakarta was established as a conservation area and became a tourist destination in Jakarta. Many things have been attempted by the government such as the improvement of public space which is to be one tourist destination for visitors to enjoy the atmosphere of the past. Above it then conducted a study to determine whether the influence of public space for the visual quality of the area, especially Kali Besar. This research uses quantitative method with post positivistic rationalist approach. The result of the research shows that there is influence of public space on visual quality in Kali Besar Jakarta area.